If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = x + (2x + 1) + (4x + 3) + (8x + 5) Reorder the terms: y = x + (1 + 2x) + (4x + 3) + (8x + 5) Remove parenthesis around (1 + 2x) y = x + 1 + 2x + (4x + 3) + (8x + 5) Reorder the terms: y = x + 1 + 2x + (3 + 4x) + (8x + 5) Remove parenthesis around (3 + 4x) y = x + 1 + 2x + 3 + 4x + (8x + 5) Reorder the terms: y = x + 1 + 2x + 3 + 4x + (5 + 8x) Remove parenthesis around (5 + 8x) y = x + 1 + 2x + 3 + 4x + 5 + 8x Reorder the terms: y = 1 + 3 + 5 + x + 2x + 4x + 8x Combine like terms: 1 + 3 = 4 y = 4 + 5 + x + 2x + 4x + 8x Combine like terms: 4 + 5 = 9 y = 9 + x + 2x + 4x + 8x Combine like terms: x + 2x = 3x y = 9 + 3x + 4x + 8x Combine like terms: 3x + 4x = 7x y = 9 + 7x + 8x Combine like terms: 7x + 8x = 15x y = 9 + 15x Solving y = 9 + 15x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 9 + 15x
| x+2+x+5=28 | | 9h-28=53 | | 8m-23=57 | | y^3-5y^2+3y-15= | | 2(5+9)=78 | | 1.3=-9 | | 2x^2+3x-40=0 | | 10-2x=3(x-2)+4 | | (3x-15)(24x-1200)=0 | | 3x=-9-18y | | e^3x=80 | | 3x+30=80 | | -9-11y= | | 3x=333 | | 5x^2+4=-9x | | (5-v)(5v+7)=0 | | 9y-2+8=3y+38+y | | -0.5(2)+3=y | | -0.5(0)+3=y | | z^4+(1-i)=0 | | -0.5(-2)+3=y | | 7t-(6-5t+(3t+4))= | | 25+13.5h-0.25h= | | t=25+13.5h-0.25h | | 2(7-z)= | | 5z-14= | | 65-6x=8 | | 1x^2-49=0 | | -9(x+5)=82 | | m^2-33n+1=0 | | X^2-12+30=0 | | 6r+4=s^2 |